Improving the hosting capacity of photovoltaic distributed generators in low voltage distribution systems by using demand response - Moreira, Saulo Gomes; Kalache, Nadya; Paschoareli, Dionizio [UNESP]; IEEE (Ieee, 2017)
In this paper real data from a smart grid deployment project were used to analyze low voltage distribution systems with different levels of photovoltaic distributed generation penetration, smart metering and then we discuss how a new energy tariff scheme can contribute to increase the grid capacity to host new distributed energy resources. The hourly capacity marginal costs model was adopted to build the new tariffs scheme in order to consider the generation profile from the photovoltaic panels. We observed that for future high photovoltaic generation penetration scenarios the proposed new energy pricing structure could avoid voltage levels surplus, rise the free capacity of the transformers, and, consequently, improve the grid's hosting capacity.
Keywords: smart grids; demand response; distributed generation; photovoltaics penetration